(untitled) (AYUSHDHARA, 2022)
An acute respiratory disease, caused by a novel corona virus(SARS-CoV-2, previously known as 2019-nCoV), the corona virus disease 2019 (COVID-19) has spread worldwide and was officially declared a global pandemic by the World Health Organization(WHO) on March 11,2020.Many patients with Covid-19 after making full recovery have a range of symptoms for weeks or months after infection, of a physiological or psychiatric nature. This Post-Covid condition is often called ‘Post-Covid Syndrome’, ‘Long Covid’ or Post-Acute Covid-19. Certain symptoms among Corona virus disease survivors such as Depression, Anxiety and Memory impairment may be related to psychological factors. In the Post-Covid psychological issues, Anxiety is a major complication of Covid-19 that may even exacerbate the infection course and the infection may intensify anxiety. Restrictions such as lockdown and social distancing are on ease throughout the globe, however some people find it difficult to re-adapt to normal life.Whether one has been infected with the virus or not, there are implications of the pandemic on our mental health. The destruction of a lifetime’s dedication to build up a small business that closed down during lockdown and not holding family members’ hands as they die add to physical and mental health impacts. Homoeopathic medicines are efficient in treating anxiety arising as a Post-Covid consequence without any side effects and complications. This review aims to analyze the Post-Covid Anxiety and the role of Homoeopathy in helping the survivors recover from such a sequel.